Big 4 Audit Fee Premiums for Auditor’s Industry Specialisation Evidence from the United Kingdom - XU, RUI (2017)
The dissertation investigates Big 4 audit fee premiums for industry specialization based on samples of PLC and Ltd which are existed in 2014 in London Stock Exchange and supplements the evidence from the United Kingdom by extending to partner level. There are fee premiums for national level, city level, joint level and partner level industry specialists. It is also found that Big 4 are dominant players in the audit market. Key words: Big 4, audit fees, audit quality, industry specialisation, the United Kingdom